Investigating the role of syncytiotrophoblast-derived extracellular vesicles in the pathogenesis of preeclampsia - Logenthiran, PV (2024)

(untitled)
Introduction: Preeclampsia (PE), a multi-systemic disorder of pregnancy affecting 2-8% of women globally, is one of the leading causes of maternal and neonatal morbidity and mortality. PE is diagnosed by de novo hypertension and end-organ damage. Although precise mechanisms are not fully elucidated, placenta is involved in the pathogenesis. Syncytiotrophoblast-derived extracellular vesicles (STB-EVs), which are membrane-bound biomolecules ranging between 30 – 1000 nm in size are gaining attention due to their diagnostic potential and their role in pathogenesis of PE. This thesis explores the roles of STB-EVs in pregnancy, focusing on the effects of their cargo (proteins and miRNA) on altering maternal physiology in PE and their potential to serve as non-invasive biomarkers. This research aimed to establish reliable protocols for isolating STB-EVs and to investigate their protein and genetic cargo, particularly focusing on kynurenine metabolising enzymes (KYNMEs) and microRNAs (miRNAs) relevant to preeclampsia.